Structural, functional and evolutionary diversity of 4-coumarate-CoA ligase in plants - Lavhale, Santosh G.; Kalunke, Raviraj M.; Giri, Ashok P. (Planta, 2018)
Main conclusions The 4-coumarate-CoA ligases (4CL) contribute in channelizing flux of different phenylpropanoid biosynthetic pathways. Expression of 4CL is optimized at developmental stages and in response to environmental triggers such as biotic and abiotic stresses. The enzyme is valuable in metabolic pathway engineering for curcuminoids, resveratrol, biofuel production and nutritional improvement. Vigorous analysis of regulation at functional and expression level is obligatory to attain efficient commercial production of candidate metabolites using 4CL. Phenylpropanoid pathway provides precursors for numerous secondary metabolites in plants. In this pathway, 4-coumarate-CoA ligase (EC 6.2.1.12, 4CL) is the main branch point enzyme which generates activated thioesters. Being the last enzyme of three shared common steps in general phenylpropanoid pathway, it contributes to channelize precursors for different phenylpropanoids. In plants, 4CL enzymes are present in multiple isoforms and encoded by small gene family. It belongs to adenylate-forming enzyme family and catalyzes the reaction that converts hydroxy or methoxy cinnamic acid derivatives to corresponding thioesters. These thioesters are further utilized for biosynthesis of phenylpropanoids, which are known for having numerous nutritional and medicinal applications. In addition, the 4CL enzymes have been characterized from various plants for their role in plant physiology or in biotic and abiotic stresses. Furthermore, specific isoforms are differentially regulated upon exposure to diverse stimuli leading to flux diversion toward the particular metabolite biosynthesis. Evolutionary studies showed that 4CL separately evolved after monocot and dicot segregation. Here, we provide a comprehensive review on 4CL, which includes evolution, function, gene/protein structure, role in metabolite biosynthesis and cellular partition, and their regulation. Based on the available data, we have explored the scope for pathway engineering by utilizing 4CL enzymes.